Background Information:

This question follows from here

It is tempting to write $$V_0(X) = \beta\left[\left(\frac{\beta^{-1}S_0 - S_1(d)}{S_1(u) - S_1(d)}\right)X(u) + \left(\frac{S_1(u) - \beta^{-1}S_0}{S_1(u) - S_1(d)}\right)X(d)\right]$$ as

$$V_0(X) = E_Q[\beta X]$$ where the expectation is taken with respect to the new purely formal probability measure $Q$ defined by $$Q(u) = \frac{\beta^{-1}S_0 - S_1(d)}{S_1(u) - S_1(d)}$$ and $$Q(d) = \frac{S_1(u) - \beta^{-1}S_0}{S_1(u) - S_1(d)}$$

Note that $Q(u) + Q(d) = 1$; $Q$ will be a probability measure provided these values are non-negative.


The quantity $\frac{S}{B}$ is called the discounted stock price. It will be useful later to notice that the pricing measure $Q$ has a special property with respect to the discounted stock price: it makes the discounted stock a martingale, i.e.,

$$\frac{S_0}{B_0} = E_{Q}[S_1/B_1]$$

I am curious on how to verify this. I assume we need to show both sides but I am not sure how to proceed.


1 Answer 1


In your setting, $\beta = B_0 B_1^{-1}$. Then \begin{align*} E_Q(S_1/B_1) &= Q(u)S_1(u)/B_1 + Q(d)S_1(d)/B_1\\ &=\frac{\beta^{-1}S_0 - S_1(d)}{S_1(u) - S_1(d)}S_1(u)/B_1 + \frac{S_1(u) - \beta^{-1}S_0}{S_1(u) - S_1(d)}S_1(d)/B_1\\ &=\frac{\beta^{-1}S_0S_1(u)/B_1 - S_1(d)S_1(u)/B_1 + S_1(u)S_1(d)/B_1-\beta^{-1}S_0S_1(d)/B_1}{S_1(u) - S_1(d)}\\ &=\beta^{-1}S_0/B_1\\ &=\frac{S_0}{B_0}. \end{align*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.